In-hospital mortality analysis of Japanese patients with acute coronary syndrome using the Tokyo CCU Network database: Applicability of the GRACE risk score. Issue 3 (March 2018) - Komiyama, Kota; Nakamura, Masato; Tanabe, Kengo; Niikura, Hiroki; Fujimoto, Hajime; Oikawa, Keiko; Daida, Hiroyuki; Yamamoto, Takeshi; Nagao, Ken; Takayama, Morimasa; ,
Abstract: Background: The GRACE risk score was developed to predict in-hospital mortality for acute coronary syndrome (ACS) using multinational registries, but did not include Japanese data. Therefore, GRACE risk scores are not extensively used in Japan. The present study aimed to evaluate the relationship between the GRACE risk score and in-hospital mortality among Japanese patients with ACS using the Tokyo CCU (cardiovascular care unit) Network Database. Methods and results: A total of 9460 patients with ACS hospitalized at 67 Tokyo CCUs between January 2011 and December 2013 were retrospectively reviewed and GRACE risk scores were calculated. Patients in the Tokyo CCU Network database had more severe conditions compared to those of the original GRACE study. There was a strong correlation between the GRACE risk score and in-hospital mortality for patients with ST-segment elevation myocardial infarction (STEMI) or non ST-segment elevation myocardial infarction (NSTEMI) ( r = 0.99, p < 0.001); however, the correlation was not significant for patients with unstable angina ( r = 0.35, p = 0.126). For STEMI + NSTEMI patients, the discrimination ability of the GRACE risk score was excellent, with a c statistic of 0.87 (95% confidence interval, 0.86–0.89). Conclusions: The GRACE risk score is a good predictor of in-hospital mortality for Japanese patients with STEMI or NSTEMI, and can help clinicians stratify patients by risk for optimal patient triage and early treatment management.